A novel strategy for fabricating (Ti, Ta, Nb, Zr, W)(C, N) high-entropy ceramic reinforced with in situ synthesized W2C particles. Issue 21 (1st November 2022) - Li, R.; Luo, R.Y.; Lin, N.; Li, A.Q.; Zhang, X.C.; Tang, Y.; Wu, Z.G.; Wang, Z.Y.; Ma, C.
Abstract: A new strategy was proposed to prepare in situ W2 C particle reinforced (Ti, Ta, Nb, Zr, W)(C, N) high-entropy ceramics by the low chemical affinity between tungsten and nitrogen elements. High-entropy ceramics were prepared by in situ carbothermal reduction-nitridation and spark plasma sintering at elevated temperatures. The inferior chemical affinity between tungsten and nitrogen resulted in the formation of the W2 C second phase in high-entropy carbonitrides during the reaction of metal oxides, carbon powder and nitrogen. The diffusion of tungsten and uniformly distributed W2 C particles in the high-entropy carbonitride matrix enhanced the mechanical properties due to the high-entropy effect and dispersion strengthening mechanism. The high-entropy ceramic sintered at 2000 °C demonstrated a high hardness of 23.46 GPa at 9.8 N and an excellent fracture toughness of 4.59 MPa m 1/2 . The proposed technique was applicable to various carbonitride ceramic systems to prepare high-performance ceramic materials.